Reliability of information recorded on the National Immunization Program Information System - José Cássio de Moraes; Ana Paula França; Ione Aquemi Guibu; Rita Barradas Barata; Adriana Ilha da Silva; Alberto Novaes Ramos Jr; Ana Paula França; Andrea de Nazaré Marvão Oliveira; Antonio Fernando Boing; Carla Magda Allan Santos Domingues; Consuelo Silva de Oliveira; Ethel Leonor Noia Maciel; et al. (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To analyze the reliability of records held on the National Immunization Program Information System (SI-PNI) in a subsample of children included in the national vaccination coverage survey in Brazilian state capitals and Federal District in 2020. Methods This was a study of agreement between data recorded on vaccination cards (doses and dates) and on the SI-PNI for 4050 children with full coverage at 24 months. Results Data on 3587 children were held on the SI-PNI, with losses of 11% (95%CI: 10;12). Total agreement between doses and dates in the two sources was 86% (95%CI: 86;87), however taking each dose and vaccine individually, variation was greater, with 32% of data in only one source. Conclusion Part of the information was not recorded, but the discrepancy can be considered small. Nonetheless, underrecording of doses and children can compromise vaccination coverage estimates, altering the numerator and denominator data.